Colloidal processing of thulium-yttria microceramics. (February 2022) - Santos, S.C.; Rodrigues, O.; Campos, L.L.
Abstract: The development of new dosimetric materials is essential for the safe and effective use of nuclear technology. In the present study, an eco-friendly bio-prototyping approach was developed for preparing thulium-yttria microceramics with potential applications in radiation dosimetry. Micro-powder compacts were obtained by casting colloidal thulium-yttria suspensions prepared with 20 vol% particles in thin-walled tube templates. Samples were sintered at 1600 °C for 2 h under the environmental pressure and atmosphere to obtain thulium-yttria microceramics with dimensions of 3.33 ± 0.01 mm × 2.27 ± 0.01 mm (height × diameter), as well as a cubic C-type structure, pycnometric density of 4.79 g cm −3 (95.61% theoretical density), and surface microstructure comprising hexagon-like grains bonded at the boundaries. The use of thulium as an activator of yttria greatly improved the electron paramagnetic resonance (EPR) response of the microceramics, where the main EPR peak (p1 ) was recorded at 351.24 mT and the g factor was 2.0046. The innovative findings obtained in this study may facilitate the production of new solid state dosimeters. Graphical abstract: Image 1 Highlights: Thulium-yttria rods produced using an eco-friendly bio-prototyping method. Thulium-yttria powder particles had a mean diameter of 96 nm. Colloidal suspensions with 20 vol% particles stabilized at pH 10.5. Sintering at 1600 °C for 2 h yielded rods with a dense microstructure. Thulium acted to enhance the electron paramagnetic resonance response of yttria.